Quo Vadis Interfaith Relations after 2016 Constitutional Court Decision - Frans Paillin Rumbi (ADI Publisher, 2020)
The 1965 Presidential Decree on the blasphemy and abuse of religion law is bad news for tribal religions. Therefore they try to maintain their existence by taking refuge in Hinduism. Some things to consider include, the similarity of elements of local beliefs and the freedom to exercise trust. Nevertheless, they still feel the government treats them discriminatively because there is no freedom to display their identity. The problem is further complicated because other religious communities tend to regard them as infidels who need to be “converted” into believing in Allah and embracing one of the official religions. The desire of adherents of tribal religions to be treated fairly gets a fresh breeze through a 2016 constitutional court ruling that allows them to empty the religious column on their electronic identity card (KTP) or other identity cards, or allow them to write their identity as “believers”; But this decision raises the question: How the relationship between adherents of universal religion and adherents of tribal religion in the midst of changes in the constitution? I use the observational methodology and theory Cosmotheandric Trinity by Raimundo Panikkar. The Constitutional Court (MK) decision is correct. The tribal religion (aluk todolo/ alukta) is pluralis. Therefore Christianity needs to redefine its mission to aluk and build respectful relationships based on the principle of difference is valued without reducing religious values ??to a universal value.